2015
DOI: 10.4209/aaqr.2014.07.0147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Particulate Matter, Ions and OC/EC in a Museum in Shanghai, China

Abstract: The size-fractionated particle number concentrations were monitored continuously in the different exhibition halls of an enclosed museum, in Shanghai. Particles in different size bins were collected to investigate the main chemical compositions. Results indicated that the mass concentrations of coarse particles, fine particles and ultrafine particles were in the range of 20.50-24.38 μg/m 3 , 23.39-24.08 μg/m 3 and 16.02-17.48 μg/m 3 , respectively. In addition, the activities of cleaning and walking can greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
3
1
0
Order By: Relevance
“…Enhanced levels of organic matter were also reported in other cultural heritage indoor environments (e.g., Cappitelli et al, 2009;Mascova et al, 2015). The predominant contribution of the sulfates, for the ionic components, is in agreement with findings at indoor cultural heritage environments (Cao et al, 2011;Xiu et al, 2015;Bartl et al, 2016;Uring et al, 2018); whereas, according to publications calcium-rich particles have been determined to dominate the indoor aerosol in museums depending on the wall material (Camuffo et al, 1999(Camuffo et al, , 2001 or restoration and construction works (Gysels et al, 2004), without excluding outdoor sources (Gysels et al, 2002). The same stands for outdoors despite the prevalence of dust relative to POM with 42.5% against 22.6%.…”
Section: Pollutant Statisticssupporting
confidence: 81%
“…Enhanced levels of organic matter were also reported in other cultural heritage indoor environments (e.g., Cappitelli et al, 2009;Mascova et al, 2015). The predominant contribution of the sulfates, for the ionic components, is in agreement with findings at indoor cultural heritage environments (Cao et al, 2011;Xiu et al, 2015;Bartl et al, 2016;Uring et al, 2018); whereas, according to publications calcium-rich particles have been determined to dominate the indoor aerosol in museums depending on the wall material (Camuffo et al, 1999(Camuffo et al, , 2001 or restoration and construction works (Gysels et al, 2004), without excluding outdoor sources (Gysels et al, 2002). The same stands for outdoors despite the prevalence of dust relative to POM with 42.5% against 22.6%.…”
Section: Pollutant Statisticssupporting
confidence: 81%
“…Results of the EC size distribution are very consistent among the different sites. Whatever the site and the season, higher EC concentrations are found in C and UF particles compared to F particles, with maximum values in UF particle as found in previous studies (Marinoni et al, 2005;Xiu et al, 2015). due to (1) decreases in EC wet deposition and concentration during the wet season and (2) the influence of long-range transport from sources such as biomass burning during the dry season.…”
Section: Ec and Oc Variationsupporting
confidence: 61%
“…Temporal variation of size resolved indoor and outdoor PM showed that main source of indoor coarse PM are visitors and fine PM infiltration from the outdoor environment (Chatoutsidou et al, 2015). Similar effect has been already described in several studies related to indoor air quality in museums (e.g., Camuffo et al, 1999;Worobiec et al, 2008;Wang et al, 2015;Xiu et al, 2015). Further, the time behavior of PM 10 concentrations measured in various parts of the hall by 3 DustTrak instrument showed that, for the purpose of modelling, the indoor environment can be considered as well mixed.…”
Section: Introductionsupporting
confidence: 60%